Enhancing surgical outcomes: the vital role of continuous support from surgical material suppliers - França, Bruno Campos de; Cunha, Artur Henrique Galvão Bruno da; Silveira, Fábio Coelho Alves; Valença, Marcelo Moraes (Avanços em Medicina, 2025)
.